The Translation Error Found In Google Translate Product - Ayuningtyas, Arina (Prosiding University Research Colloquium, 2020)
The objective of this study was to describe the errors made in the Indonesian text into English text by Google Translate. This study employed one translation of Indonesian Narrative texts taken from internet made by using Google Translate. Those samples were taken by using purposive sampling technique. The categorizations of translation errors were adapted from Keshavarz (1999) and Vilar et al. (2006). The errors can occur in the grammatical errors, lexical errors and semantic errors. The data gathered were analyzed descriptively by using qualitative approach. The data source was found in Internet. The findings of the analysis showed that there were 3 categories of translation errors obtained from 17 data. Ranking from the most common to the least common errors found in the data, they were grammatical errors (76%) and lexical errors (24%). The data findings also showed that statistical method of Google Translate, the inability of Google Translate to understand the contexts of the texts beyond sentence, and errors in the source texts that carried into translation errors in the target texts were the causes of translation errors found in the data.